Long- and short-term temporal stability of complex fractionated atrial electrograms in human left atrium during atrial fibrillation. - Scherr D; Dalal D; Cheema A; Nazarian S; Almasry I; Bilchick K; Cheng A; Henrikson CA; Spragg D; Marine JE; Berger RD; Calkins H; et al. (Journal of Cardiovascular Electrophysiology, 2009)
Background: Complex fractionated atrial electrograms (CFAEs) have been reported as targets for catheter ablation of atrial fibrillation (AF). However, the temporal stability of CFAE sites remains poorly defined. Methods and Results: The study consisted of two phases. In the initial phase, two automated software algorithms, namely the interval confidence level (ICL) and the average interpotential interval (AIPI) were assessed for their diagnostic accuracy for automated CFAE detection. The AIPI was found to be superior to the ICL, and an AIPI of <=100 ms was associated with a sensitivity and specificity of both 92% for detection of CFAEs. In the second phase of the study, 12 patients (2 females, mean age 54 ± 12 years) who underwent catheter ablation for persistent AF were studied to investigate the temporal stability of CFAEs. Two consecutive left atrial (LA) three-dimensional CFAE maps coded with AIPI readings were reconstructed during ongoing AF in each study patient, with a mean time difference of 34.3 ± 8.7 minutes between the two maps. Among a total of 149 CFAE sites and 238 non-CFAE sites on the first CFAE map that were precisely revisited during the repeat mapping process, 135 (90.6%) and 225 (94.5%) remained as CFAE sites and non-CFAE sites, respectively. RF ablation at the selected stable CFAE sites significantly prolonged AF cycle length (181 ± 26 ms to 199 ± 29 ms, P < 0.0001). Conclusion: CFAEs recorded in the LA during AF display high temporal stability in patients with persistent AF. The clinical significance of our findings warrants further investigation.